Гемодинамічний супровід тиротропних ефектів бальнеотерапії на курорті Трускавець - Фучко, О.Л. (Медична гідрологія та реабілітація, 2010)
Прослежены сопутствующие изменения параметров центральной и интракардиальной гемодинамики, зарегистрированных методом двумерной эхокардиографии, при выявленных ранее разных типах тиротропных эффектов бальнеотерапии на курорте Трускавець. Обнаружена умеренная корреляционная каноническая связь (R=0,40) между вызванными биоактивной водой Нафтуся изменениями тироидного статуса и гемодинамики в покое и при мышечной нагрузке. It is investigated accompanying changes of parameters central and intracardial hemodynamic, registered by method echocardiography, at revealed before different types of thyreotropic effects of balneotherapy on spa Truskavets' at the women with hyperplasia of thyreoide gland. The moderate canonical correlation (R=0,40) between caused by bioactive water Naftussya changes of thyreoid status and hemodynamic in rest is found out and at muscular loading.